Study On Smartphone GPS Navigation Applications Satisfaction Among Tourists In Malaysia - Bintang Fajar, Muhammad Sultan (2020)
Smartphone users increased tremendously in Malaysia in the las ten years. As smariphone users depend more on sophisticated and intelligent mobile devices to assist them in their daily lives for better decision making, this has prompted developers to develop more mabile applications suitable for them. One of the popular mobile application development is ush Global Positioning System (GPS) for navigation purposes. Most of the smartphone user especially tourists utilize these GPS navigation applications for traveling purposes because of those applications, inexpensive, easy to access, and user-friendly. Google Maps is one of the frecly available and popular GPS ravigation application that is used by around nine million users in the world. Past researches on GPS navigation applications were mostly system and mobile application devel: However, there are lacks of studies done on the f gle Maps as a GPS navigation application popular among its user. While previous researchers hinted at the nect to study on the factors that affect user satisfaction of mobile applications. Tl measurement for each factor in the other satisfaction model of mobile applications cannot be used dircetly and needed to be modified for GPS navigation applications measurement specifically. Hence, this study aims to fill in this gap by investigating the factors that affect the user safisfaction of GPS navigation applications among smartphone users in Malaysia and identify the relationship between the factors with the safisfaction of GPS navigation application’s user. Additionally, this study examines the effects of experience fowards the relationship between the factors and the user satisfaction of GPS navigation applications. A total of 402 tourists in Malaysia were selccted to answer the questionnaires. The Statistical Package for Social Science (SPSS) version 23.0 analysis began with exploratory analysis. to analyze the factors that affected the user satisfaction of GPS navigation applications and followed by multiple regression analysis o test their relationship and hypotheses. The results showed that system quality, information quality, perceived valu, and perceived usefulness were significantly influencing user satisfaction of GPS navigation applications, furthermore perceived usefulness was the most influencing factor that affected. user satisfaction of GPS navigation application. In addition, the experience had played Google Maps and its technolog ments usin significant moderating effects on the relationship between perceived value and user satisfaction. Therefore, this research elps future researches and software development company to understand in-depth defails of the factors that affect user satisfaction of GPS navigation applications, as well the body of knowledge for satisfaction research for mobile applications. A qualitative inquiry is needed to get more in-depth responses on why and how GPS navigation applications can improve more traveling experience for better decision making,